USING E-LEARNING IN TEACHING PROCESS - Вірстюк, Н. Г.; Оринчак, М. А.; Човганюк, О. С.; Вакалюк, І. І.; Гаман, І. О.; Василечко, М. М.; Александрук, Д. П.; Артеменко, Н. Р.; Краснопольський, С. З.; Лучко, О. Р.; Кобітович, І. М.; Гохкаленко, М. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Implementation of electronic forms of educational information into the learning process is a part of the modern educational area’s reformation. The aim of the study was to investigate the impact of innovative technologies on constant updating of universities educational environment, an improving the state of teaching and increasing of quality of knowledge and practical skills of students. To achieve this goal there was created a computer class at the Internal Medicine of Stomatological Faculty Dentistry Department named by Professor M. M. Berezhnytskiy of Ivano-Frankivsk National Medical University. Integration of project MUMEENA is effectively implemented into the learning process. The students can study methods of investigation of the respiratory (basic and adverse respiratory sounds) and cardio-vascular (auscultation of the heart in normal and pathology) systems, model of heart disease with the following introduction of acquired abilities and skills into practical medical and diagnostic process at the bedside. Thus, today we can use a new way of future doctor’s formation, as electronic forms of educational information submission complement traditional learning methods and provide an opportunity to increase the effectiveness of teaching and the level of abilities and practical skills of the students. They develop and form clinical thinking of future doctors, provide integral scientific knowledge, learn to synthesize the information and help to implement the project MUMEENA integration into the educational process.